2012
DOI: 10.2131/jts.37.863
|View full text |Cite
|
Sign up to set email alerts
|

Focused DNA microarray analysis for sex-dependent gene expression of drug metabolizing enzymes, transporters and nuclear receptors in rat livers and kidneys

Abstract: -Cytochrome P450(CYP)s are known to show a sexual dimorphic expression in rat livers. However, the comprehensive analysis for the sex-dependent gene expressions of drug metabolizing enzymes except for CYPs, transporters and nuclear receptors in rat livers and kidneys has not been investigated yet. The purpose of the present study was to identify the novel drug metabolizing and pharmacokinetics (DMPK)-related gene(s) which show the sex difference in the mRNA expressions in rat livers and kidneys. Total RNAs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To summarize, pharmacokinetics of gentiopicroside and swertiamarin in rats are subject to a gender effect, which could give rise to individual differences in drug efficacy and toxicity if it translates to human. It has been reported that the activity of most CYP enzymes are significantly lower in female rats than in male rats,[21,22] which may explain the gender difference in the pharmacokinetics of gentiopicroside and swertiamarin observed in this study. However, further studies are required to explore the mechanism of this gender effect to better understand the pharmacokinetic profiles of gentiopicroside and swertiamarin.…”
Section: Resultsmentioning
confidence: 53%
“…To summarize, pharmacokinetics of gentiopicroside and swertiamarin in rats are subject to a gender effect, which could give rise to individual differences in drug efficacy and toxicity if it translates to human. It has been reported that the activity of most CYP enzymes are significantly lower in female rats than in male rats,[21,22] which may explain the gender difference in the pharmacokinetics of gentiopicroside and swertiamarin observed in this study. However, further studies are required to explore the mechanism of this gender effect to better understand the pharmacokinetic profiles of gentiopicroside and swertiamarin.…”
Section: Resultsmentioning
confidence: 53%
“…Sex differences in CYPs and UGTs expression levels were reported in animal models . Higher paracetamol glucuronide levels were reported in female than in male rats , and recently, higher ugt1a9 expression in females was reported in liver and kidney from different rat strains, suggesting that it is not a strain‐related observation . The observed dimorphic propofol glucuronidation metabolism might be involved in the therapeutic effect of propofol as a significant, prolonged anaesthetic effect that was observed in rodents with a mixture of propofol and glucuronide inhibitor compared to their littermate without glucuronide inhibitor .…”
Section: Discussionmentioning
confidence: 95%
“…In humans, morphine is metabolized by isozymes in the uridine 5’-diphosphoglucuronosyltransferase (UGT) 1 and 2 subfamilies, with almost all preferentially synthesizing M3G over M6G (~45–55% and 15% of metabolized product, respectively; [64]). Importantly, sex differences in the expression of UGT1 and 2 subclasses of enzymes have been reported in humans [65] and rats [66]. Further, these enzymes metabolize, and are directly influenced by, steroid hormones [67].…”
Section: Discussionmentioning
confidence: 99%